Vital rates of small reef corals are associated with variation in climate. Issue 3 (9th December 2020) - Edmunds, Peter J.
Abstract: With coral cover declining on most tropical reefs, efforts are intensifying to understand the mechanisms by which environmental stressors are driving populations into demographic deficit. Here, the population dynamics of sexual cohorts of small corals (≤ 4 cm diameter) in St. John, US Virgin Islands were used to test the hypothesis that the association of vital rates with environmental conditions has changed over 22 yr. The annual fate of 3999 corals at six sites and 7–9 m depth were used to populate Leslie Matrices and calculate assemblage growth rates ( λ, without recruitment), mortality of the smallest corals, and graduation from the largest size class. Vital rates were tested for associations with temperature, the number of days with seawater warmer than 29.4°C (i.e., hot days), and rainfall. Transition probabilities varied among years, and usually more corals remained in their original size class than moved among size classes. Corals in the smallest size class had the highest mortality rate (42% yr −1 ), λ had a grand mean of 0.688, and there were trends for λ to vary with the number of hot days and rainfall through quadratic relationships. The linear dependence of λ on rainfall over consecutive 3‐yr periods declined over two decades, suggesting that this colony size‐defined coral assemblage has undergone phenotypic change in their responsiveness to varying environmental conditions.